Temporary Migrants From Egypt: How Long Do They Stay Abroad? - Ira N. Gang; Thomas K. Bauer (Institute for the Study of Labor (IZA), 1998)
This paper analyzes the determinants and timing of return migration. Special attention is given to the role of social and informational migration networks. A simple theoretical model of temporary migration demonstrates that the effect of migration networks on optimal migration duration is ambiguous. Using a sample of return migrants from six different villages in Egypt we investigate the determinants of migration duration using a flexible parametric proportional hazard model for discrete duration data. Controlling for human capital and demographic characteristics of the migrants and economic indicators for the host country, the estimation results show that informational networks have a statistically significant negative effect on migration duration.
Keywords: J61; 330; return migrants; duration of migration; Internationale Wanderung; Rückwanderung; Ägypten